Spiritual leadership and unethical pro-organisational behaviour in Pakistan’s hospitality industry - Aziz, Aisha; Akram, Kashif; Fernando, Yudi; Ur Rehman, Shafique; Wahyuni-Td, Ika Sari (Emerald Publishing, 2025)
Purpose: Drawing on social exchange theory and social identity theory, this paper aims to examine the impact of spiritual leadership on unethical pro-organisational behaviour (UPB) facilitated by high-tech devices in workplace environments. This investigation examined various contributing factors, including workplace spirituality and incivility, while also exploring the moderating role of employees’ moral courage. Design/methodology/approach: To achieve this objective, data were collected from 400 employees in Pakistan’s hospitality and tourism industry using a purposive sampling method. The data were gathered through the administration of structured questionnaires. Partial least squares structural equation modelling (PLS-SEM) was used to analyse the data. Findings: The findings indicated that perceived spiritual leadership plays a role in preventing hospitality employees from engaging in unethical practices in a work environment. While spiritual leadership enhances spirituality and reduces incivility in the hospitality sector, workplace incivility acts as a mediator in the relationship between spiritual leadership and UPB. Moreover, spiritual leadership enhances workplace spirituality, thereby mitigating the occurrence of workplace burnout. In addition, the results suggest that moral courage reduces UPB among hospitality employees by fostering workplace spirituality and reducing workplace incivility. Practical implications: Due to the morally challenging environments they navigate, employees in the tourism and hospitality sectors frequently encounter significant ethical dilemmas. Often, employees use high-tech devices to report unethical behaviour to their employers, a scenario that constitutes UPB. Originality/value: Spiritual leadership is adopted to address workplace incivility and unethical behaviour. Similarly, moral courage helps recognise employees as more accountable individuals by reducing their UPB.